Analisis Perencanaan Agregat dalam Produksi Makanan Berbahan Ayam Ras Pedaging pada UMKM Rumah Makan Selayang - Sembiring, Fernando; Hidayati, Nurul; Zahra, Nisa (IPB University, 2025)
This study aims to analyze aggregate planning strategies in the production process of broiler-based food products at the MSME Rumah Makan Selayang. Demand fluctuations cause an imbalance between production and consumption, resulting in overstock in March of up to 75 kg and stockout in May, June, July, October, and December. A quantitative approach was employed using production and sales data from January to December 2024. Primary data were obtained through direct observation of the production process and in-depth interviews with the owner, cashier, and kitchen staff, while secondary data consisted of business documentation, sales and production records, financial reports, and supporting literature. Demand forecasting was carried out using Double Exponential Smoothing, Trend Analysis, and Holt-Winters Exponential Smoothing, and analyzed using Minitab Statistical Software 22. The results show that the Holt-Winters method is the most accurate (MAD: 11.57; MAPE: 2.72 percent; MSE: 161.88). For aggregate planning strategies, chase, level, and mixed approaches were modeled using Microsoft Excel. The findings indicate that the chase strategy is the most efficient option, with a total aggregate cost of Rp3,441,109,000, because it adjusts production volume to demand and minimizes inventory. These findings provide practical guidance for food-sector MSMEs to optimize production planning, reduce inventory costs, and mitigate the risks of overstock and stockout.